A Study on Community Unit Scale Construction in China Under the Orientation of Green Production - Rui Zhang; Qingjian Zeng; Yanhang Lv; Huanjie Liu; Lixian Shi; Yukun Zhang (Land)
Based on the principle of distributed layout, the community is chosen as the basic unit of the city, and an appropriate community scale is redefined based on the attributes and characteristics of green production. This article first summarizes the existing research models at the community level using bibliometric methods, and on this basis the process of researching the green productive community unit scale is constructed. Subsequently, the data on the scales of agriculture, energy, transport, and commercial facilities from the relevant Chinese national city standards are summarized, classified, and generalized. This is followed by the derivation of appropriate grid scales for green productive community units. Ultimately, a quadratic optimization scale was devised for community units at varying levels based on fractal and management unit theory. This paper presents a new community unit scale constructed for use in large- and medium-sized areas in China, which serves as an illustrative example. The newly developed community scale has the potential to improve the efficiency of resource allocation and support the transition from functional adjustment to structural adjustment in urban areas. Furthermore, the scale definition method and principle can be extended and applied to other large- and medium-sized urban areas globally.